Republic of Armenia. - Dept., International Monetary Fund. Middle East and Central Asia (IMF Staff Country Reports., 2015)
This 2014 Article IV Consultation highlights that after a steady recovery during 2010-12 from the deep 2009 recession, Armenia's growth softened in 2013 and has remained subdued in 2014. The softening of economic activity has been broad based, as growth of exports and remittances slowed, and government spending was lower than budgeted. Construction, which had declined since the 2009 crisis, was relatively flat. Growth is projected at 2.6 percent in 2014 and is expected to increase only gradually in 2015 and over the medium term in light of expectations of slow growth in key trading partners. The authorities' policies remain geared toward maintaining macroeconomic stability and fostering sustainable and inclusive growth.